Perioperative Outcomes of Minimally Invasive Esophagectomy After Neoadjuvant Immunotherapy for Patients With Locally Advanced Esophageal Squamous Cell Carcinoma - Cheng, Jiahan; Guo, Minzhang; Yang, Yushang; Liu, Yilin; Hu, Weipeng; Shang, Qixin; Li, Chuan; Xia, Liang; Wang, Yun; Wang, Wenping; Tian, Dong; Yuan, Yong; et al. (Frontiers in Immunology, 2022)
Background Immunotherapy has become a pillar of advanced solid tumors treatment. Patients are more likely to benefit from neoadjuvant immunotherapy compared with traditional neoadjuvant therapy. However, the safety and efficacy of neoadjuvant immunotherapy for the treatment of locally advanced, surgically resectable Esophageal squamous cell carcinoma (ESCC) remain unknown. Method ESCC patients who received neoadjuvant treatment following minimally invasive esophagogastrostomy were enrolled from June 2020 to September 2021. The characteristics of neoadjuvant treatment and surgery were investigated to determine the safety and efficacy of the neoadjuvant combination of chemotherapy and immunotherapy (NCI). Results A total of 149 patients were included in the study. Patient ratio was 40:109 between NCI and neoadjuvant chemotherapy plus radiotherapy (NCR) groups. No significant difference was found in terms of pathological characteristics, including ypN stage, ypTNM stage, differentiation, lymphovascular invasion, perineural invasion, pathological complete regression and tumor regression score, and these parameters were not correlated with NCI or NCR (all p>0.05). Regarding to the operation, the NCI group had less blood loss (49.25 ± 13.47 vs. 57.02 ± 47.26, p<0.001), and shorter operation time (247.75 ± 28.28 vs. 285.83 ± 52.43, p<0.001) than the NCR group. Additionally, the NCI group demonstrated a lower rate of overall perioperative complications (p=0.003) and grade >2 perioperative complications (p=0.042) than the NCR group. Conclusion Overall, the findings reported here indicate NCI could result in better outcome and less complications to locally advanced ESCC patients compared with NCR therapy. As a novel therapeutic option, the efficacy and safety of NCI appears to be feasible and safe, while long-term survival data is still needed.